El estilo de la ley - Barahona Novoa, Alberto Autor 23795; Quesada Vargas, María Autora 28919; Rivera Chacón, Marta Autora 28920; Solano Solano, María Rosa Autora 28921 (San José, CR: Asamblea Legislativa, 1995)
Manual práctico para la confección y entendimiento de las leyes.